Assistive Technology to Fulfill the Digital Human Rights of Persons with Disabilities in Indonesia - Siti Nurhayati; Kardi Kardi; Muhammad Fawaizur Rahman; Souad Ezzerouali (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
This article analyzes the challenges to achieving digital human rights equality for people with disabilities in Indonesia and evaluates the role of assistive technologies in addressing these issues. Digital human rights are recognized under international law and affirmed by the Indonesian Constitution, which obligates the state to protect and fulfill these rights. Using a normative juridical method based on secondary data and deductive analysis, the research identifies major obstacles, including limited inclusive digital platforms, discrimination, insufficient data on disability populations and needs, restricted access to information, and ongoing rights violations. The findings show that assistive technologies, such as KIAD, Hear Me, DIGI-EDVOT, TeDi, Dif-able, and I-CHAT, significantly enhance digital accessibility for individuals with physical and sensory disabilities. The research recommends that government policies be expanded to provide assistive technologies for people with mental and intellectual disabilities to reduce existing disparities and strengthen digital inclusivity.